Exploring Phytochemicals from Ricinus Communis for Potential Therapeutic Applications in Rheumatoid Arthritis: An in-Silico Approach - Gurusowmyasri Kota (International Journal of Bioinformatics and Computational Biology, 2025)
Aim: Rheumatoid arthritis (RA) is a long-term autoimmune condition characterized by the immune system mistakenly attacking the joints, leading to swelling, discomfort, and joint deformities. Current management strategies include anti-rheumatic drugs and biologics, which have limitations. This study aims to explore the therapeutic potential of Ricinus communis (castor bean plant) phytochemicals as plant-based therapies for autoimmune conditions, like RA. Methods: Phytochemicals from Ricinus communis were retrieved using the IMPPAT database, identifying 95 compounds. Their drug-like properties were evaluated using the SwissADME tool, resulting in the selection of seven compounds: Ricinine, Apigenin, Glycolic acid, Shikimic acid, Nicotinamide, threo-9, 10-Dihydroxystearic acid, and uric acid. Toxicity assessments were conducted using the protox tool. Molecular docking was performed with pyrx to evaluate interactions was achieved using BIOVIA. Results: This study revealed that Ricinus communis Phytochemicals demonstrated strong binding affinities with autoimmune pathway-related proteins 1A8M and 1TNF, indicating significant anti-inflammatory and immunomodulatory potential. These findings suggest their promise as plant-based therapeutic agents for RA. Conclusion: This research underscores the promising anti-inflammatory and immunomodulatory properties of phytochemicals derived from Ricinus communis. The identified compounds exhibit favorable drug-like and safety profiles, with significant binding to autoimmune pathway-related proteins. These findings provide a foundation for experimental studies and the development of plant-based therapies for autoimmune disorders, such as RA.
Keywords: Anti-inflammatory; Immunomodulatory; Phytochemicals; Ricinus communis; autoimmune disorders; molecular docking; rheumatoid arthritis